Komunikasi Sambung Rasa as a Government Communication in 1983-1999 - Suryaningsih, Rosita Budi; Mulyatari, Dwi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Komunikasi Sambung Rasa is a communication form that used by Indonesian’s government at 1983 until 1999. This research will be figure about Komunikasi Sambung Rasa and why this communication system is choosen by the government. This research reveals the idea form of Komunikasi Sambung Rasa and how important to choose the right communication system, which is suitable by the people and the condition of the country. With historical method, this problems will be analyze with historical step by heuristic, verification, intrepretaion, dan historiography. This research will be reveals that Komunikasi Sambung Rasa is one of the effective communication from the government to enlightment and give information to the people, so the people feels involved and feels they are part of the government policy. This research is expected to be a documentation that Indonesia has been applied this communication system that called Komunikasi Sambung Rasa and show how effective it was. But in the end of this period, there are different goal and the information to spread.